2018
DOI: 10.17219/acem/74539
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis ofmyocardium inmouse model of diabetic cardiomyopathy using the iTRAQ technique

Abstract: These results suggest that DCM shows differences in its proteomics compared to normal controls. Our quantitative proteomic analysis may provide a new insight into the distinct molecular profile of DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Our interrogation of independent RNA expression data and western blot data shows consistent upregulation in Sorbs2 across a range of myocardial diseases, as has been recently noted. 73 Further, Sorbs2 protein is upregulated in LVNC, 8 diabetic cardiomyopathy, 6 and is released from infarcted myocardium. 4 Upregulation is potentially mediated by Mef2 transcription factors, 74 although posttranscriptional regulation by disease-relevant microRNAs and RNA-binding proteins may also contribute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interrogation of independent RNA expression data and western blot data shows consistent upregulation in Sorbs2 across a range of myocardial diseases, as has been recently noted. 73 Further, Sorbs2 protein is upregulated in LVNC, 8 diabetic cardiomyopathy, 6 and is released from infarcted myocardium. 4 Upregulation is potentially mediated by Mef2 transcription factors, 74 although posttranscriptional regulation by disease-relevant microRNAs and RNA-binding proteins may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Prior reports indicate that Sorbs2 expression is altered in the setting of myocardial infarction and diabetic cardiomyopathy, and its suppression in vitro induces cardiomyocyte hypertrophy. [4][5][6] In addition, recent in vivo studies suggest both pathogenic and protective roles for Sorbs2 in the development of arrhythmogenic right ventricular cardiomyopathy (ARVC) 7 and left ventricular non-compaction (LVNC). 8 Specifically, Ding et al reported that global Sorbs2 knockout mice (KO) develop lethal ARVC with severe right ventricle (RV) failure at 4-6 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…SORBS2 was closely related to cell adhesion, and it localized in actin stress fibers [ 32 ]. Proteomics analysis presented that SORBS2 was obviously upregulated in the diabetic cardiomyopathy model [ 33 ]. And another study suggested SORBS2 involved in DN progression through regulating actin filaments [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research using proteomic analysis of myocardial tissue has identified new pathophysiological mechanisms contributing to cardiovascular diseases such as ischemic cardiomyopathy [ 15 ], dilated cardiomyopathy (DCM) [ 14 ], diabetic cardiomyopathy [ 17 , 18 ], and atherosclerosis [ 19 ]. Recently, we showed changes in platelet proteins, such as clusterin, CXC-motif-chemokine, cathepsin, creatine-kinase-B and myotrophin, to be associated with cellular, biologic, metabolic, immune, and coagulation system processes involved in the development of CHF caused by MMVD in dogs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%